Once upon a time in the West : essays on the politics of thought and imagination - Zwicky, Jan, 1955- (McGill-Queen's University Press, 2023)
"Western civilization is over. So begins Jan Zwicky's trenchant exploration of the roots of global cultural and ecological collapse: a way of thinking that is also linked to some of the West's most noted achievements. The Renaissance merged imperial enterprise with Islamic algebra and recently recovered Greek mathematics to precipitate mechanized industry and resource extraction; these in turn made possible the growth of capitalism, the military-industrial complex, and Big Technology. Despite its self-image as objective, Zwicky argues, the West's style of thought is not politically neutral, but intensely anthropocentric. It has led those who adopt it to regard the more-than-human world as nothing more than timber licences and drilling sites, where value is not recognized unless it is monetized. Oblivious to context and blind to big-picture thinking, it analyzes, mechanizes, digitizes, and systematizes, while rejecting empathy and compassion as distorting influences. Lyric comprehension, in Zwicky's view, offers an alternative to this way of thinking, and she provides a wide range of examples. Once Upon a Time in the West documents how a narrow epistemological style has left Western thought blind to critical features of reality, and how the terrifying consequences of that blinkered vision are now beginning to unfold."--